ESTIMASI KAPASITAS TAMPUNG DAN POTENSI NILAI NUTRISI DAUN NENAS DI PT. GREAT GIANT PINEAPPLE TERBANGGI BESAR SEBAGAI PAKAN RUMINANSIA - Andy Ringgita; Liman ,; Erwanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The aim of this research is to know the potential and the capasities of pineapple’s leaves in PT. Great Giant Pineapple Terbanggi as the ruminant’s feed. This research was held in June 2013 until August 2013 in PT. Great Giant Pineapple Terbanggi Besar, Central Lampung. This research uses the ‘purposive sampling’ survey method. The data that would be used in this research consists of the primary data and secondary data. The Primary data encompasses all information about the plantations that become the object of the research, for example, the planting area, the harvested area, the production wastes that will be produced and the wastes management. The secondary data is a data that can be obtainable from the existing literature, including the information about the existing potential estates in Terbanggi Besar, Central Lampung. The results of this research shows that the total wastes of the pineapple’s leaves in PT. Great Giant Pinneapple is ± 9.000 kg/ha. Carrying capacity for ruminant is 53.152 UT per year (40% assuming feed) and with 42.553 UT per year (50% assuming feed) can fulfill the necessity as alternative of ruminant’s feed. (Keywords: Pineapple’s leaves, Carrying capacity, Potential nutrition).